Generalised Periodontitis: A Behavioural Management - ABDUL HAYEI, NUR AYMAN; MAT BAHARIN, NOR HALIZA (Malaysian Journal of Science Health & Technology, 2021)
Generalised periodontitis occurs due to long-standing gingivitis and often presented with poor plaque control. Periodontal stability is challenging when the patient has poor oral hygiene habits and fear of dental treatment. It requires systematic and effective behavioural management on top of traditional periodontal therapy in the overall management of the patient. It is crucial to manage dental anxiety as this could affect patient’s compliance. A familiarly seen generalised periodontitis may not have fully succeeded without behavioural support. This is a case of a 35-year-old woman with dental anxiety; undergoing a change in her old incorrect oral hygiene habit to improve self-plaque control.